Evaluation of the Countenance Stake Model Program For The Implementation of Bogor Scouts At An-Nur Darunnajah 8 Cidokom Bogor West Java - Tri Yulianto (al-fikrah: Jurnal Manajemen Pendidikan, 2023)
Coaching is essentially an activity or activity that is carried out consciously, planned, directed and organized responsibly in order to develop and improve, abilities and resources available to achieve goals. This research is a way to evaluate the Cub Scout Leader program at An-Nur Darunnajah 8 Cidokom Islamic Boarding School This research is an evaluation research with the Countenace Stake model. Data collection using techniques, observation, interviews and documentation. The analysis technique used is descriptive qualitative. This research uses a qualitative approach with descriptive methods supported through data collection techniques in the form of observation, interviews and documentation. Interviews were conducted with Majlis daily Coordinator and Scoutmaster. Based on this research, the planning of scout coaches has been conceptualized very well, it can be calculated at 100%, because it is in accordance with the central government guidelines. In terms of implementation obtained with a good category, it can be calculated at 88.89%. Of the four aspects evaluated including: Program Implementation, Process Planning, Implementation of the Cub Scout coaching process, Process Assessment, almost all aspects have been fulfilled by the An-Nur Darunnajah 8 Islamic Boarding School. The evaluation results show that all aspects of the results of the evaluation of the implementation or implementation of the Cub Scout Leader Role program have been fulfilled by the An-Nur Darunnajah 8 Islamic Boarding School. Obtained in the sufficient category, can be calculated at 75%. This can be seen from the existence of skills between students and scout coaches as well as the timeliness of the coaches and the presence of coaches in learning.